Effects of once-weekly subcutaneous retatrutide on weight and metabolic markers: A systematic review and meta-analysis of randomized controlled trials - Eric Pasqualotto; Rafael Oliva Morgado Ferreira; Matheus Pedrotti Chavez; Alexandre Hohl; Marcelo Fernando Ronsoni; Tales Pasqualotto; Francisco Cezar Aquino de Moraes; Larissa Hespanhol; Janine Midori Figueiredo Watanabe; Carine Lütkemeyer; Simone van de Sande-Lee (Metabolism Open)
Aim: To assess the effects of once-weekly subcutaneous retatrutide on weight and metabolic markers and the occurrence of side effects in patients with overweight, obesity and/or type 2 diabetes (T2D). Methods: PubMed, Embase, Cochrane Library, and ClinicalTrials.gov databases were systematically searched for placebo-controlled, randomized clinical trials (RCTs) published up until February 23, 2024. Weighted mean differences (WMDs) for continuous outcomes and risk ratios (RRs) for binary endpoints were computed, with 95 % confidence intervals (CIs). Results: A total of three studies were included, comprising 640 patients, of whom 510 were prescribed retatrutide. Compared with placebo, retatrutide significantly reduced body weight (WMD -10.66 kg; 95 % CI -17.63, −3.69), body mass index (WMD -4.53 kg/m2; 95 % CI -7.51, −1.55), and waist circumference (WMD -6.61 cm; 95 % CI -13.17, −0.05). In addition, retatrutide significantly increased the proportion of patients who achieved a weight reduction of ≥5 % (RR 2.92; 95 % CI 2.17–3.93), ≥10 % (RR 9.32; 95 % CI 4.56–19.06), ≥15 % (RR 18.40; 95 % CI 6.00–56.42), and ≥20 % (RR 16.61; 95 % CI 4.17–66.12). Conclusions: In this meta-analysis, the use of once-weekly subcutaneous retatrutide was associated with a significant reduction in body weight and improvement of metabolic markers in patients with overweight, obesity and/or T2D, compared with placebo, with an increase in non-severe gastrointestinal and hypersensitivity adverse events. Phase 3 RCTs are expected to shed further light on the efficacy and safety of once-weekly subcutaneous retatrutide over the long term.